Marketing Study of Customer Loyalty in Georgia and Its Impact on Hospitality Business: Case of Imereti Region (European Journal of Marketing and Economics, 2023)
Businesses, including the hospitality sector, discovered the importance of customer maintenance as a key success factor.  This study aims to investigate the impact of customer satisfaction, experience, and loyalty in Georgia, particularity in Imereti Region.  Results indicate that a significant relationship exists between service quality attributes and customer satisfaction. Results conjointly revealed that service quality results in satisfying customers and customers’ satisfaction results in customer loyalty. Hotel managers should offer better services to their customers for gaining a competitive advantage, and it will facilitate them to guide the market with efficiency. Market orientation produces a positive effect on customer loyalty, which in turn has a positive effect on business performance, showing that market orientation has a significant and positive indirect effect on business performance.
Keywords: Costumer loyalty, management, marketing, performance, service